2002
DOI: 10.1080/1042819021000040116
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Associated with Lactic Acidosis

Abstract: Type B lactic acidosis is rare among patients with malignant diseases. To date only one case report has documented lactic acidosis occurring in a patient with multiple myeloma (MM). Our patient, a 55-year-old black man, was diagnosed with stage IIIA immunoglobulin G-kappa (IgG-kappa) MM in September 1995. He was found to have severe lactic acidosis at the time of second relapse. During the terminal phase of his disease, he required multiple hospitalizations for management of lactic acidosis and other complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…There is evidence for altered carbohydrate metabolism in some cancer cells with increased glycolytic activity [56]. Interestingly, we and others have noted the improvement in lactate levels with disease remission [55]. Finally, Type B lactic acidosis may be caused by decreased clearance of lactate from extensive liver involvement by tumor [57].…”
Section: Malignancymentioning
confidence: 90%
“…There is evidence for altered carbohydrate metabolism in some cancer cells with increased glycolytic activity [56]. Interestingly, we and others have noted the improvement in lactate levels with disease remission [55]. Finally, Type B lactic acidosis may be caused by decreased clearance of lactate from extensive liver involvement by tumor [57].…”
Section: Malignancymentioning
confidence: 90%
“…There are many reports in the literature of patients with HM who have lactic acidemia independent of systemic oxygenation and organ perfusion, due to tumor-related lactic acid production and the prevalence of hyperlactatemia in patients with HM is unknown. [34][35][36][37][38][39][40][41] Thus, generalizing the utility of serum lactate measurements without prospective validation to a patient population that may experience higher basal serum lactate levels may subject these patients to inappropriate ICU transfer and aggressive resuscitation strategies. Our study addressed this clinical equipoise and extends the validity of current critical care guidelines to HM patients by providing evidence that lactic acid A power calculation suggested that matching controls to cases in a 4:1 ratio would achieve 80% power (α = 0.05) to detect an association (OR ≥ 2.5) between elevated serum lactate levels and the development of septic shock within 48 h of FN.…”
Section: Methodsmentioning
confidence: 99%
“…Concurrent hypoglycemia and hyperlactatemia secondary to enzootic bovine lymphosarcoma in a cow is unusual. Lactic acidosis is a rare and highly fatal complication of hematopoeitic neoplasms in human patients with a 7% survival rate with chemotherapy 2–7 . The precise mechanism is unknown but defective glycolytic processes, liver failure, and renal failure all have been implicated 3 .…”
mentioning
confidence: 99%
“…There are sporadic reports of hypoglycemia and lactic acidosis occurring in people secondary to malignant neoplasms 2–7 . Forty‐three of 53 patients with lactic acidosis secondary to leukemia and lymphoma had hepatic involvement and 20 of 53 had hypoglycemia 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation